The influence of the use of website-based learning media on engineering drawing materials - Tuti Suartini; Aan Sukandar; Fikran Fauzul Zadi; Anggraili Salsabila Fikadinda; Wahid Maulana (Informasi, 2022)
The era of digitalization actually offers various conveniences. Learning can be done through various methods, not only conventional methods. The widespread use of the internet network must be utilized optimally in various fields. So that digital technology is very functional today to do online learning. The influence of the production of learning media with website-based technology on responses to the learning activities of the Engineering Drawing course, Mechanical Engineering Education Department. Learning media used through the web aims to be used as alternative teaching materials in the learning process in the hybrid learning era. The technology used allows users to access it on any device that has an internet network without having to eat up storage on the device, because the media only uses the internet network to access it. In the research conducted using quantitative descriptive methods. The results showed that the media user response results obtained a percentage of 80.54% which could be categorized as very good. Based on the conclusions of the research results, this web-based learning media is feasible to use because it can help the teaching and learning process both offline anoonline